BIMBINGAN DAN PENYULUHAN TENTANG PENTINGNYA BAURAN PROMOSI BAGI PENGEMBANGAN USAHA FURNITURE SUN MEUBEL DI JALAN.SUDIMORO RT.06/RW.07 KOTA MALANG - Helmy Adi Saksana (Jurnal Pengabdian Kepada Masyarakat (J-ABDIMAS), 2016)
The purpose of Community Service is to: a.Increase knowledge and ability of the Entrepreneur in the field of operations, especially the field of practical promotional mix. b.increase application of education and training results in the framework of science and technology development. c. Creating opportunities for employment opportunities in the governance of community economic activities in the form of increased incomes of the community, while the benefits of this activity is so that entrepreneurs can: a. price decent.b.Enhance of the main source of income of entrepreneurs. c. Services easily known to customers or potential customers. d. Creating wider employment opportunities. Enterprises can be developed.The method of implementation offered is face to face by:a. The lecture, which covers the theory of the importance of the marketing mix. b.Discustion, which is associated with the importance of apple marketing mix. c.Training makes the marketing mix easy and practical. d.Problems / cases, based on the experience of entrepreneurs so far.